Constructive Computation in Stochastic Models with Applications The RG-Factorization - Li, Quan-Lin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Constructive Computation in Stochastic Models with Applications: The RG-Factorizations" provides a unified, constructive and algorithmic framework for numerical computation of many practical stochastic systems. It summarizes recent important advances in computational study of stochastic models from several crucial directions, such as stationary computation, transient solution, asymptotic analysis, reward processes, decision processes, sensitivity analysis as well as game theory. Graduate students, researchers and practicing engineers in the field of operations research, management sciences, applied probability, computer networks, manufacturing systems, transportation systems, insurance and finance, risk management and biological sciences will find this book valuable. Dr. Quan-Lin Li is an Associate Professor at the Department of Industrial Engineering of Tsinghua University, China.
Stochastic Models -- Block-Structured Markov Chains -- Markov Chains of GI/G/1 Type -- Asymptotic Analysis -- Markov Chains on Continuous State Space -- Block-Structured Markov Renewal Processes -- Examples of Practical Applications -- Transient Solution -- Quasi-Stationary Distributions -- Markov Reward Processes -- Sensitivity Analysis and Evolutionary Games.
Keywords: Mathematics; Computer communication systems; Mathematical optimization; Operations research; Management science; Probabilities; Industrial engineering; Production engineering; Quality control; Reliability; Industrial safety; Mathematics; Probability Theory and Stochastic Processes; Computer Communication Networks; Optimization; Operations Research, Management Science; Industrial and Production Engineering; Quality Control, Reliability, Safety and Risk; Electronic books